Subclinical Atrial Fibrillation in Older Patients. Issue 14 (3rd October 2017) - Healey, Jeff S.; Alings, Marco; Ha, Andrew; Leong-Sit, Peter; Birnie, David H.; de Graaf, Jacob J.; Freericks, Michel; Verma, Atul; Wang, Jia; Leong, Darryl; Dokainish, Hisham; Philippon, Francois; et al.
Abstract : Background: Long-term continuous electrocardiographic monitoring shows a substantial prevalence of asymptomatic, subclinical atrial fibrillation (SCAF) in patients with pacemakers and patients with cryptogenic stroke. Whether SCAF is also common in other patients without these conditions is unknown. Methods: We implanted subcutaneous electrocardiographic monitors (St. Jude CONFIRM-AF) in patients ≥65 years of age attending cardiovascular or neurology outpatient clinics if they had no history of atrial fibrillation but had any of the following: CHA2 DS2 -VASc score of ≥2, sleep apnea, or body mass index >30 kg/m 2 . Eligibility also required either left atrial enlargement (≥4.4 cm or volume ≥58 mL) or increased (≥290 pg/mL) serum NT-proBNP (N-terminal pro–B-type natriuretic peptide). Patients were monitored for SCAF lasting ≥5 minutes. Results: Two hundred fifty-six patients were followed up for 16.3±3.8 months. Baseline age was 74±6 years; mean CHA2 DS2 -VASc score was 4.1±1.4; left atrial diameter averaged 4.7±0.8 cm; and 48% had a prior stroke, transient ischemic attack, or systemic embolism. SCAF ≥5 minutes was detected in 90 patients (detection rate, 34.4%/y; 95% confidence interval [CI], 27.7–42.3). Baseline predictors of SCAF were increased age (hazard ratio [HR] per decade, 1.55; 95% CI, 1.11–2.15), left atrial dimension (HR per centimeter diameter, 1.43; 95% CI, 1.09–1.86), and blood pressure (HR per 10 mm Hg, 0.87; 95% CI, 0.78–0.98), but not prior stroke. The rate of occurrence of SCAF in those with a history of stroke, systemic embolism, or transient ischemic attack was 39.4%/y versus 30.3%/y without ( P =0.32). The cumulative SCAF detection rate was higher (51.9%/y) in those with left atrial volume above the median value of 73.5 mL. Conclusions: SCAF is frequently detected by continuous electrocardiographic monitoring in older patients without a history of atrial fibrillation who are attending outpatient cardiology and neurology clinics. Its clinical significance is unclear. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01694394. Abstract : Supplemental Digital Content is available in the text.